Heat and mass transfer studies of palm kernel cake (PKC) in ﬂuidized bedfermenter - Foong, Chee Woh; Krishnaiah, K. (Elsevier, 2009)
Solid state fermentation (SSF) which involves the growth of microorganism on moist solid substratesin the absence of free ﬂowing water, has gained renewed attention over submerged fermentation forspeciﬁc applications. During the SSF process in fermenter, there are three main engineering problemsencountered such as the removal of metabolic heat from the substrate, diffusion of O2 and moisturethrough the substrate, and heterogeneity of the substrate and inoculum. A ﬂuidized bed fermenter inwhich the particles move independently like a ﬂuid was proposed to conduct the study. Throughoutthe study, rapid heat transfer from PKC to air was experimentally observed within the ﬁrst 150s with atemperature drop of 30◦C. This indicated that the excellent heat transfer between palm kernel cake andairallowssolidstatefermentationofPKCwithoutaccumulationofmetabolicheatinthefermenter.Apartfrom heat removal, water adsorption study on PKC from air to bed was carried out.It showed that theincreaseofadsorbedwaterinPKCwasproportionaltoairrelativehumidityandinverselyproportionaltosuperﬁcial air velocity. The maximum moisture content adsorbed by PKC under ﬂuidization conditionswas around 10% (on dry basis). Finally, mathematical models for heat and mass transfer were proposedwhich can predict the experimental data quite satisfactorily